First evidence of pyrethroid resistance in Italian populations of West Nile virus vector Culex pipiens. Issue 3 (9th April 2022) - Pichler, Verena; Giammarioli, Carola; Bellini, Romeo; Veronesi, Rodolfo; Arnoldi, Daniele; Rizzoli, Annapaola; Lia, Riccardo Paolo; Otranto, Domenico; Ballardini, Marco; Cobre, Pietro; Serini, Paola; della Torre, Alessandra; et al.
Abstract: Culex pipiens (Linnaeus), one of the most abundant mosquito species in Europe, plays a crucial role in the endemic transmission of West Nile virus and caused the large outbreak with >1600 human cases in 2018. Although evidence of resistance to pyrethroids has been reported for Cx. pipiens populations from Spain and Greece, resistance monitoring has been largely neglected in Italy. Herein, we investigate susceptibility of Italian Cx. pipiens populations to the pyrethroids permethrin and deltamethrin. Results from WHO‐tube‐bioassays revealed mortalities ranging from 14–54%, indicating high levels of resistance, in four out of 10 populations exposed to permethrin (0.75%) and of 63% in one of three populations exposed to deltamethrin (0.05%). Reduced susceptibility (mortality<98%) was detected in almost all other populations. A clear association is shown between the resistant phenotype and the presence of kdr ‐alleles in position 1014 of the VSSC, strongly suggesting its role in reducing susceptibility. The study provides the first evidence of pyrethroid‐resistance in Italian Cx. pipiens populations and reports levels of resistance paralleled in the European region only in Turkey. This highlights the urgent need to implement insecticide‐resistance management plans to restore the efficacy of the nowadays only chemical weapon available to control arbovirus transmission in Europe. Abstract : We report the first evidence of Pyrethroid resistance in Italian Culex pipiens populations. The resistance phenotype appears to be substantial and widespread possibly affecting the effectiveness of pyrethroid treatments in case of arbovirus outbreaks. The kdr ‐mutation L1014F within the VSSC appears to be one of the mechanisms underlying resistance.